THE INFLUENCE OF THE GOVERNMENT'S INTERNAL CONTROL SYSTEM ON THE REALIZATION OF GOOD UNIVERSITY GOVERNANCE MODERATED BY DIGITAL TRANSFORMATION (SURVEY OF HIGHER EDUCATION UNITS IN CENTRAL SULAWESI) - Betty, Betty; Ridwan, Ridwan; M. Iqbal A; Femilia, Femilia; Fikry, Fikry (Bajang Institute, 2024)
This research aims to test and analyze